Analisis Pengenaan Pajak Final dan Non Final Pada Perusahaan Jasa Konstruksi Di BEI - Tjahjono, Mazda Eko Sri (JAK (Jurnal Akuntansi) : Kajian Ilmiah Akuntansi, 2016)
This study was conducted to determine the difference between the taxation of non tax -finals and final. This study uses the data of financial statements that have been published during the period 2010-2014 ( five years).. Statistical methods in this study using normality test , homogeneity test , ANOVA test and Independent t- Test.Based on the results of statistical analysis that there are significant differences between the taxation of non tax -final and final in determining the amount of tax payable. Final taxation significantly greater than the taxation of non-final. For the government, the final taxation considered to be very beneficial because it can increase revenue sources in state finances. However, on the other hand for compulsory considered to be very harmful because the final taxation does not pay attention to the costs incurred in obtaining such income.Keywords : Final Tax, Tax non-final, obtain fee, state revenue